Answer: Choice B)
2x+5(2x+3) = 3
============================================
Reasoning:
We start with the second equation 2x+5y = 3
Since y = 2x+3 from the first equation, we can replace every copy of y with (2x+3). This replacement is valid because y and 2x+3 are the same.
So that's how we go from 2x+5y = 3 to 2x+5(2x+3) = 3
This replacement is done to get rid of the y variable, and it allows us to solve for x later on.
Estimated would be 700 x 80
Simplifying
x + 0.7 = 1 + -0.2x
Reorder the terms:
0.7 + x = 1 + -0.2x
Solving
0.7 + x = 1 + -0.2x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '0.2x' to each side of the equation.
0.7 + x + 0.2x = 1 + -0.2x + 0.2x
Combine like terms: x + 0.2x = 1.2x
0.7 + 1.2x = 1 + -0.2x + 0.2x
Combine like terms: -0.2x + 0.2x = 0.0
0.7 + 1.2x = 1 + 0.0
0.7 + 1.2x = 1
Add '-0.7' to each side of the equation.
0.7 + -0.7 + 1.2x = 1 + -0.7
Combine like terms: 0.7 + -0.7 = 0.0
0.0 + 1.2x = 1 + -0.7
1.2x = 1 + -0.7
Combine like terms: 1 + -0.7 = 0.3
1.2x = 0.3
Divide each side by '1.2'.
x = 0.25
Simplifying
x = 0.25
I only know 1 way.
Answer:
f(x) = (x - 6)/(3/2)
Step-by-step explanation: